Comparison of ductal stenting versus surgical shunts for palliation of patients with pulmonary atresia and intact ventricular septum. Issue 7 (23rd February 2015) - Mallula, Kiran; Vaughn, Gabrielle; El‐Said, Howaida; Lamberti, John J.; Moore, John W.
<x xml:space="preserve">Abstract</x> Objectives We sought to compare ductal stenting (DS) to systemic‐pulmonary artery shunt (SPS) in a contemporary cohort of patients having pulmonary atresia with intact ventricular septum (PAIVS). Background Alternative palliative strategies (interventional versus surgical) are currently available for initial palliation of ductal dependent patients with various forms of congenital heart disease. There is little data available to guide strategy selection. Methods A retrospective review of patients with PAIVS at our institution from Jan 2006 to Dec 2013 was performed. Demographic, echocardiographic, procedural, and follow‐up data were reviewed and analyzed. Results Twenty‐nine patients were identified. Thirteen underwent DS and 16 underwent SPS. In the DS group, 6 had radiofrequency perforation of the pulmonary valve, and 12 underwent balloon pulmonary valvuloplasty (BPV) prior to DS. SPS was performed after perforation of the pulmonary valve in 1 patient and after BPV in 4 patients. Procedural success was 92.8% in the DS group versus 93.3% in the SPS group. In the DS group, one patient required emergency shunting due to intra‐procedural ductal spasm. In the SPS group there was one procedure related death, and there were six significant procedure‐related complications. Five patients required re‐interventions prior to hospital discharge. The median length of hospital stay for the DS versus SPS group was 10 versus 23 days, respectively (P < 0.05). Post discharge, there were seven reinterventions in the DS group and two reinterventions in the SPS group. Conclusions DS may provide a safe and effective alternative to SPS in selected patients with PAIVS. © 2015 Wiley Periodicals, Inc.